2008
DOI: 10.1242/jeb.017947
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular mechanisms of osmoregulatory plasticity in killifish after seawater transfer

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 69 publications
(105 reference statements)
5
43
0
1
Order By: Relevance
“…1C,D). The population divergence revealed by freshwater challenges is consistent with other studies, but the population variation revealed by brackish water challenges is not (Scott et al, 2008Scott and Schulte, 2005). Scott et al (2004) reported F. heteroclitus population divergence in Cl − regulation following freshwater challenges.…”
Section: Results and Discussion Physiological Acclimationsupporting
confidence: 89%
See 1 more Smart Citation
“…1C,D). The population divergence revealed by freshwater challenges is consistent with other studies, but the population variation revealed by brackish water challenges is not (Scott et al, 2008Scott and Schulte, 2005). Scott et al (2004) reported F. heteroclitus population divergence in Cl − regulation following freshwater challenges.…”
Section: Results and Discussion Physiological Acclimationsupporting
confidence: 89%
“…Scott et al (2004) reported F. heteroclitus population divergence in Cl − regulation following freshwater challenges. However, previous high-salinity challenges showed no loss of osmolyte balance and no difference between northern and southern populations (Scott et al, 2008;Scott and Schulte, 2005 (Whitehead et al, 2012b). Thus, we find that osmotic challenges spanning the salinity threshold across which gills are remodeled (∼1 p.p.t.)…”
Section: Results and Discussion Physiological Acclimationmentioning
confidence: 46%
“…Surprisingly, baseline expression of the 'seawater' isoform NKA-1b of Na + ,K + -ATPase (Richards et al, 2003;Bystriansky et al, 2006) did not differ between the two salinities ( Fig.9G), but there are two other reports where this was also the case (Shrimpton et al, 2005;Kiilerich et al, 2007). The higher expression of NKCC1a in SW trout (Fig.9H) is consistent with the SW-adaptive role of this basolateral transporter in net NaCl extrusion (McCormick, 2001;Tipsmark et al, 2002;Scott et al, 2005;Scott et al, 2008;Kiilerich et al, 2007). Control NHE2 expression was also greater in SW trout (Fig.9D); there have been many studies of this apical transporter in various teleosts (reviewed by Ivanis et al, 2008), but the only previous salinity study suggested that expression of NHE2 transiently increased after transfer from brackish water to FW in the killifish (Scott et al, 2005).…”
Section: Differences In Baseline Gene Expression Between Fw and Sw Troutmentioning
confidence: 53%
“…While knowledge of the basic physiology of fishes with respect to ion and water regulation has progressed greatly from the first historic investigations (Smith, 1930;Keys, 1931;Krogh, 1937), most studies have been based on constraining fish to controlled environments and in many cases subjecting them to single step changes in salinity (e.g. Katoh et al, 2008;Scott et al, 2008;Madsen et al, 2009). However, in nature, these animals are capable of movement throughout their habitats, and they may rapidly encounter a variety of salinities.…”
Section: Introductionmentioning
confidence: 99%